PLURALITAS DAN TANTANGAN MISI: KERANGKA KONSEPTUAL UNTUK PENDIDIKAN AGAMA KRISTEN DALAM MASYARAKAT MAJEMUK - Fransiskus Irwan Widjaja (Program Studi Pendidikan Agama Kristen, 2019)
The purpose of this paper is to see plurality and mission as a conceptual framework in Christian religious education. Building pluralism is an appeal to accept pluralism is an order of people who understand each other that in essence they are a unity in diversity. Pluralism is a condition where there are various things. Religious pluralism explain